2015
DOI: 10.1136/jmedgenet-2014-102964
|View full text |Cite
|
Sign up to set email alerts
|

A novel syndrome of Klippel-Feil anomaly, myopathy, and characteristic facies is linked to a null mutation inMYO18B

Abstract: Deficiency of MYO18B is linked to a novel developmental disorder which combines KFA with myopathy. This suggests a widespread developmental role for this gene in humans, as observed for its murine ortholog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…Seven genes harbored ≥ 2 variants of which only two (CWF19L1 and MYO18B) harbored two variants predicted to be damaging according to SIFT (score o0.05) and Polyphen2 (score 40.85) or resulted in a premature stop codon. MYO18B is unlikely to cause ARCA as variants in this gene are associated with lung cancer 9 or linked to Klippel-Feil anomaly and myopathy, 10 which were not present in our patient. However, during the course of our studies, CWF19L1 was reported as a novel cause of ARCA 3 and we focused further on this gene.…”
Section: Resultsmentioning
confidence: 55%
“…Seven genes harbored ≥ 2 variants of which only two (CWF19L1 and MYO18B) harbored two variants predicted to be damaging according to SIFT (score o0.05) and Polyphen2 (score 40.85) or resulted in a premature stop codon. MYO18B is unlikely to cause ARCA as variants in this gene are associated with lung cancer 9 or linked to Klippel-Feil anomaly and myopathy, 10 which were not present in our patient. However, during the course of our studies, CWF19L1 was reported as a novel cause of ARCA 3 and we focused further on this gene.…”
Section: Resultsmentioning
confidence: 55%
“…The recent identification of MYO18B mutations in patients exhibiting symptoms of nemaline myopathy has, however, provided circumstantial evidence for a role of MYO18B in skeletal myogenesis; consistent with this, muscle biopsy analyses revealed defects in sarcomeric organization (Alazami et al 2015;Malfatti et al 2015) reminiscent of those seen in the cardiomyocytes of Myo18B mutant mice (Ajima et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…In the first of these, two patients with Klippel-Feil anomaly (KFA) were found to be homozygous for a nonsense mutation in the penultimate exon of the MYO18B gene (Alazami et al 2015); notably, both patients exhibited symptoms of myopathy (hypotonia and muscle weakness), a condition not previously associated with KFA. Muscle biopsy analysis of one patient revealed variation in fiber size and a loss of normal banding indicative of a loss of thick filaments.…”
mentioning
confidence: 99%
“…A list of known genes (Supplemental Table 1) was constructed from multiple online database resources (http:// www.omim.org/, http://www.mnglabs.com/tests/, http://www. ncbi.nlm.nih.gov/pubmed) or abstracted from recently published articles (2,3,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Deleterious variants in the known arthrogryposis-associated genes were identified in 17 of 48 (35.4%) unrelated families (Table 1).…”
Section: Resultsmentioning
confidence: 99%